Elementary and multielementary representations of vectroids - Belousov, K. I.; Nazarova, L. A.; Roiter, A. V.; Sergeychuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove that every finitely represented vectroid is determined, up to an isomorphism, by its completed biordered set. Elementary and multielementary representations of such vectroids (which play a central role for biinvolutive posets) are described.